Electric machines : analysis and design applying Matlab - Cathey, Jimmie J. (Boston : McGraw-Hill, 2001)
Integrates the computer software MATLAB to handle the calculations in electric machine analysis. This work helps readers to calculate and plot performance data through the use of developed computer software for each energy conversion. It offers a web site that includes a downloadable version of solution manual and MATLAB M-files.
1 Introduction 2 Sinusoidal Steady-State Circuits 3 Magnetic Circuits and Energy Conversion 4 Transformers 5 DC Machines 6 Induction Motors 7 Synchronous Machines Appendix A Winding Factors Appendix B Conversion Factors Appendix C Magnetic Wire Tables
Includes bibliographical references and index.
Keywords: Electric machinery -- Computer-aided design; Electric machinery -- Design and construction -- Computer programs; MATLAB